Sensitivity and Specificity of Vascular Endothelial Growth Factor A (VEGF-A) against Endometriosis - Heriyadi Manan; Edo Rezaldy Edward (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background. Endometriosis is a benign disorder defined by the presence of endometrial glands and stroma outside the uterus. Endometriosis occurs in 10-15% of women during their reproductive years. Angiogenesis and the inflammatory response are important factors in the development of endometriosis. The formation of a new blood supply is a crucial step in the formation of endometrial lesions. Angiogenesis is induced by a growth factor peptide, namely vascular endothelial growth factor A (VEGF-A). VEGF-A is known as a vascular permeability factor that plays an important role in the pathological angiogenesis process and is a more specific and prominent angiogenesis factor among the VEGF family. The purpose of this study was to determine the sensitivity and specificity of examination VEGF-A of menstrual blood in diagnosing endometriosis compared to laparoscopy. Methods. This diagnostic test research has been carried out at the gynecology polyclinic, especially the division of Fertility, Endocrinology and Reproduction, Faculty of Medicine, Sriwijaya University- Dr. Central General Hospital. Mohammad Hoesin from August to November 2018, there were 45 patients who met the inclusion criteria. VEGF-A examination in instrumental blood based on ELISA examination. Data analysis to measure sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy using Medcalc statistics. Results. From the results of this study, it is known that the majority of the study samples were aged 31.69 years (24-38 years) 75.6%, body mass index (BMI) 51.1% with normal BMI, experienced infertility by 82.2% of the sample, most of the samples did not smoke (95.6%) and most experienced mild pain 55.6% using the VAS pain scale. From this study, it is known that 84.4% or 38 of the study samples had endometriosis with a cut off point value of VEGF-A > 347 pg/mL. From the results of this study, it is known that the sensitivity of VEGF-A in diagnosing endometriosis is 84.2%, specificity is 85.7%, positive predictive value is 97%, negative predictive value is 50% and accuracy is 84%. Conclusion. VEGF-A menstrual blood can be used as a diagnostic tool for endometriosis.